2012
DOI: 10.1371/journal.pone.0029724
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Drugs and Incident Open-Angle Glaucoma: A Population-Based Cohort Study

Abstract: BackgroundOpen-angle glaucoma (OAG) is a progressive neurodegenerative disease that may lead to blindness. An elevated intraocular pressure (IOP) is its major risk factor. OAG treatment is currently exclusively directed towards the lowering of the IOP. IOP lowering does not prevent disease progression in all patients and thus other treatment modalities are needed. Earlier studies reported cholesterol-lowering drugs to have neuroprotective properties. The aim of this study was to determine the associations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 41 publications
2
66
1
10
Order By: Relevance
“…Statins are also known to reduce transendothelial migration. Interestingly, some studies have shown that long-term statin use appears to be associated with a reduced risk of open-angle glaucoma (78,79). However, given both the robust and long-term efficacy of a single dose of xray radiation in preventing cellular entry into the optic nerve and retina, it will be important to further evaluate the use of x-rays for preventing glaucoma and other inflammatory conditions.…”
Section: Figurementioning
confidence: 99%
“…Statins are also known to reduce transendothelial migration. Interestingly, some studies have shown that long-term statin use appears to be associated with a reduced risk of open-angle glaucoma (78,79). However, given both the robust and long-term efficacy of a single dose of xray radiation in preventing cellular entry into the optic nerve and retina, it will be important to further evaluate the use of x-rays for preventing glaucoma and other inflammatory conditions.…”
Section: Figurementioning
confidence: 99%
“…If lifestyle changes prove to be beneficial in modifying glaucoma risk in a safe manner, they can prove difficult to incorporate into one's life. New medications such as statins, which not only improve a vascular profile in general but also have neuroprotective properties and improve endothelial cell dysfunction, may be used in the future for the treatment of glaucoma after more is understood about this disease process [44,131].…”
Section: Five-year Viewmentioning
confidence: 99%
“…24 Most of these abnormalities are related to the elevation of intraocular pressure (IOP) causing damage to the optic nerve head directly. 25 However, given that at least some glaucoma patients have a normal or relatively low IOP range, other systemic conditions, such as diabetes, cardiovascular disease, and obesity, may also be relevant. 26,27 Numerous previous studies have described the involvement of primary open-angle glaucoma and normal-tension glaucoma in patients with OSAS.…”
mentioning
confidence: 99%